Macroporous Three-Dimensional PDMS Scaffolds for Extrahepatic Islet Transplantation. Issue 7 (July 2013) - Pedraza, Eileen; Brady, Ann-Christina; Fraker, Christopher A.; Molano, R. Damaris; Sukert, Steven; Berman, Dora M.; Kenyon, Norma S.; Pileggi, Antonello; Ricordi, Camillo; Stabler, Cherie L.
Clinical islet transplantation has demonstrated success in treating type 1 diabetes. A current limitation is the intrahepatic portal vein transplant site, which is prone to mechanical stress and inflammation. Transplantation of pancreatic islets into alternative sites is preferable, but challenging, as it may require a three-dimensional vehicle to confer mechanical protection and to confine islets to a well-defined, retrievable space where islet neovascularization can occur. We have fabricated biostable, macroporous scaffolds from poly(dimethylsiloxane) (PDMS) and investigated islet retention and distribution, metabolic function, and glucose-dependent insulin secretion within these scaffolds. Islets from multiple sources, including rodents, nonhuman primates, and humans, were tested in vitro. We observed high islet retention and distribution within PDMS scaffolds, with retention of small islets (<100 μm) improved through the postloading addition of fibrin gel. Islets loaded within PDMS scaffolds exhibited viability and function comparable to standard culture conditions when incubated under normal oxygen tensions, but displayed improved viability compared to standard two-dimensional culture controls under low oxygen tensions. In vivo efficacy of scaffolds to support islet grafts was evaluated after transplantation in the omental pouch of chemically induced diabetic syngeneic rats, which promptly achieved normoglycemia. Collectively, these results are promising in that they indicate the potential for transplanting islets into a clinically relevant, extrahepatic site that provides spatial distribution of islets as well as intradevice vascularization.